Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/jxb/eraa470
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signalling in plant nanobiology: current status and perspectives

Abstract: Plant nanobiology as a novel research field provides scientific basis for the agricultural use of nanoparticles (NPs). Plants respond to the presence of nanomaterials by synthesizing signal molecules, such as the multifunctional gaseous nitric oxide (NO). Several reports have described the effects of different nanomaterials (primarily chitosan NPs, metal oxide NPs and carbon nanotubes) on endogenous NO synthesis and signalling in different plant species. Other works have demonstrated the ameliorating effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…This scheme of CNTs and visible light can be used to introduce NO in plants in a controlled manner. Similarly, not only the positive regulation for MWCNTs was recently reported in seedlings of rapeseed but also the seedlings ameliorated salt stress by the involvement of NO (Kolbert et al, 2021).…”
Section: Carbon Nanotubes (Cnt)supporting
confidence: 67%
See 1 more Smart Citation
“…This scheme of CNTs and visible light can be used to introduce NO in plants in a controlled manner. Similarly, not only the positive regulation for MWCNTs was recently reported in seedlings of rapeseed but also the seedlings ameliorated salt stress by the involvement of NO (Kolbert et al, 2021).…”
Section: Carbon Nanotubes (Cnt)supporting
confidence: 67%
“…Thus, among them, it was found that the modification of amine groups of chitosan by diethylenetriamine resulted in high NO loadings (Qun et al, 2008). Recently, CS-NPs have been reported to be effective in increasing the redox potential of Camellia sinensis and positively regulating the seed germination of pearl millet (Kolbert et al, 2021).…”
Section: Chitosan (Cs) Npsmentioning
confidence: 99%
“…Signaling molecules such as nitric oxide (NO) are found in all plants and implicated in various physiological, biochemical, and developmental processes, as well as responses to abiotic stress ( Hajihashemi et al., 2020b ; Kolbert et al., 2021 ). NO serves as a messenger of stress signals.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the reverse is true and that applying gibberellic acid induces the endogenous synthesis of H 2 S, reducing oxidative damage by boron toxicity [ 104 ]. · NO has also been associated with plant responses to nanomaterials (NMs), either in the induction of tolerance to stress by NMs or in the plant response to stress caused by NMs [ 105 ].…”
Section: Ronss In Plant Metabolismmentioning
confidence: 99%